An Analysis on Contemporary Chinese Youth’s Standard of Love and Marriage from Song ‘No Car No House’ - Tongdaeng, Tattanit; Fan, Mingxin; Hou, Wanrong (Journal of International Studies, Prince of Songkla University, 2017)
This article aimed to study the Chinese young people’s love and marriage standard in nowadays through analyzing content of song ‘No car No House’ and the critical issues toward this song, as well as analyzing other related documents. The study found that, 1) song ‘No car No House’ reflected bachelor problem of Chinese young people in nowadays and their view about love standard. 2) The serious unbalance in proportion of male and female population was the main reason for the bachelor problem of urban young people, their own desire and selection become second. 3) Chinese young people’s love standard in nowadays tended to be materialism, especially in female’s view. Moreover, since in last ten years the marriage cost was getting high, which put contemporary young men under an extreme pressure.